The effects of Artemisia Sieberi, Achillea Fragrantissima, and Olea Europaea leaves on the performance and physiological parameters in heat-stressed broiler chickens - Mahasneh, Zeinab M. H.; Abuajamieh, Mohannad; Abdelqader, Anas; Al-Qaisi, Mohmmad; Abedal-Majed, Mohamed A.; Al-Tamimi, Hosam; Zakaria, Hana; Al-Fataftah, Abdur-Rahman A. (Frontiers in Veterinary Science, 2024)
High temperatures have detrimental effects on the performance and physiology of broiler chickens. Medicinal plants have various biological activities and may enhance the heat resistance of chickens during heat waves. Therefore, this study aimed to explore the potential roles of using specific local medicinal plants to alleviate the negative impacts of heat stress (HS) in broilers. In this study, 180 day-old chicks were used to investigate the effects of HS and dietary indigenous medicinal plants on growth performance, antioxidant biomarkers, and intestinal health. The chicks were assigned to six groups (18 pens with 10 chicks per pen) with three replicates each. In the first group, the chicks were kept under thermoneutral conditions (CON) and fed a basal diet. The other five groups were exposed to recurrent heat stress and fed a basal diet (T1, HS group) or supplemented with Artemisia Sieberi (1.25 g/kg of feed; T2), Achillea Fragrantissima (15 g/kg of feed; T3), Olea europaea (10 g/kg of feed; T4), and all the previous additives (all-in-one) combined at the same dose levels mentioned above (T5). At 21 days of age, the chicks from each group were exposed to two phases of heat stress: phase 1 from days 21 to 34 (34 ± 1°C) followed by phase 2 from days 35 to 39 (37 ± 1°C). The results indicate that HS significantly increased rectal temperature and respiration rate in broiler chickens. Feed intake and body weight gain were improved in all supplemented groups, while the feed conversion ratio was decreased in response to the dietary inclusion of medicinal plants. Additionally, glutathione peroxidase and immunoglobulin G levels were increased in the T3, T4, and T5 groups compared to the other groups. HS induced significant upregulated in the mRNA levels of heat shock protein 70 and interleukin-8, while the mRNA of occludin was decreased. The T3, T4, and T5 showed significantly decreased expression of hepatic HSP70 and ileum IL-8 genes and increased ileum mRNA occludin levels relative to the CON and T1 groups. In conclusion, supplementation with these plants enhances growth performance and maintains intestinal health sustaining the productivity of broiler chickens under HS conditions.